2019
DOI: 10.20944/preprints201908.0038.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STAT3 and STAT5 Activation in Solid Cancers

Abstract: The Signal Transducer and Activator of Transcription (STAT)3 and 5 are activated by many cytokine receptors to regulate specific gene expression and mitochondrial functions. Their role in cancer is largely context dependent as they can both act as oncogenes and tumor suppressors. We review here the role of STAT3/5 activation in solid cancers and summarize their association to survival in cancer patients. The molecular mechanisms that underpins the oncogenic activity of STAT3/5 signaling includes the regulation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…STAT family members can act as both oncogenes and tumor suppressors. Therefore, the use of the STAT family as a diagnostic and prognostic basis requires careful consideration of each specific cancer type and the characteristics of each patient 8,29 …”
Section: Discussionmentioning
confidence: 99%
“…STAT family members can act as both oncogenes and tumor suppressors. Therefore, the use of the STAT family as a diagnostic and prognostic basis requires careful consideration of each specific cancer type and the characteristics of each patient 8,29 …”
Section: Discussionmentioning
confidence: 99%
“…Oncogenes also mediate ROS production by regulating NOXs expression. Signal transducer and activator of transcription 3 (STAT3) increases NOX4 expression [80]; mutant KRAS activates NOX1 and downregulates antioxidant enzymes, including SOD2, catalase, and Prxs [81,82]; and Ras-related C3 botulinum toxin subunit 1 (Rac1) can stimulate the production of mitochondrial superoxide and participate in the assembly and activation of NOX1 and NOX3 [83][84][85][86]. Tumor suppressor p53 and forkhead box O (FOXO) family transcription factors can prevent oxidative stress by inducing the expression of antioxidant genes.…”
Section: •−mentioning
confidence: 99%
“…p-STAT3 is able to increase the expression levels of certain target genes, including vascular endothelial growth factor (VEGF), Cyclin D1 and Bcl-xL, etc [9][10][11][12]. STAT3 constitutively activation is frequently observed in cancers, including lung cancer, liver cancer, gastric cancer and renal cell carcinoma [13]. Increasing number of studies show that STAT3 may serve as one of the oncogenic critical factors and is associated with a poor prognosis in certain types of cancer.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Increasing number of studies show that STAT3 may serve as one of the oncogenic critical factors and is associated with a poor prognosis in certain types of cancer. For instance, it has been reported that elevated STAT3 expression is associated with poor prognosis in gastric cancer, lung cancer and live cancer [13]. Additionally, STAT3 has been revealed to be crucial involved in cancer cell proliferation, invasion, migration and apoptosis [14,15].…”
Section: Ivyspring International Publishermentioning
confidence: 99%